2018
DOI: 10.1111/jcpp.12909
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of psychopathology in extremely low birth weight survivors from early adolescence to adulthood: a 20‐year longitudinal study

Abstract: Extremely low birth weight survivors experienced a blunting of the expected improvement in depression and anxiety from adolescence to adulthood. These findings suggest that altered physiological regulatory systems supporting emotional and cognitive processing may contribute to the maintenance of internalizing problems in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 59 publications
1
25
0
Order By: Relevance
“…Generally, the greater persistence of problems over time in this study compared with other very and extremely low birth weight cohorts [2,14,16,30,39] may also be related to the greater neurodevelopmental immaturity at birth, higher risk for neonatal brain injury and reduced neurodevelopmental plasticity that is conferred by birth at extremely low gestations compared with birth after 26 weeks of gestation. Indeed, moderate/severe cognitive impairment, an index of such factors [40,41], accounted for some of the difference in the overall behavioral problems with those having cognitive difficulties having persistently greater problems, but did not explain the excess entirely.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Generally, the greater persistence of problems over time in this study compared with other very and extremely low birth weight cohorts [2,14,16,30,39] may also be related to the greater neurodevelopmental immaturity at birth, higher risk for neonatal brain injury and reduced neurodevelopmental plasticity that is conferred by birth at extremely low gestations compared with birth after 26 weeks of gestation. Indeed, moderate/severe cognitive impairment, an index of such factors [40,41], accounted for some of the difference in the overall behavioral problems with those having cognitive difficulties having persistently greater problems, but did not explain the excess entirely.…”
Section: Discussionmentioning
confidence: 71%
“…The few longitudinal studies that have investigated the prevalence of behavioral symptoms or disorders in children and adolescents who were born preterm or low birth weight have shown that the increased prevalence of problems persists over time and may have greater stability in individuals born preterm compared with those born at term or with normal birthweight [2,[12][13][14][15][16]. Many of these previous studies employed cross-sectional analysis techniques which are not able to detect variation in individual trajectories; or they focussed on specific disorders such as ADHD.…”
Section: Introductionmentioning
confidence: 99%
“…Existing research has identified sensitive parenting in childhood [ 5 ] as a potential resilience factor for academic achievement among very preterm children (i.e., in very preterm children sensitive parenting was more strongly associated with academic outcomes than in term born children). By contrast, a recent study reported that very preterm children may be more strongly affected by risk factors for mental health such as family dysfunction, parental mental health problems, and peer victimisation while not benefitting as much from potential resilience factors such as number of close friends or sensitive parental care compared to term born children [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Preterm birth is closely associated with increased risk of neurodevelopmental, cognitive and psychiatric impairment that extends across the life course (Nosarti et al, 2012; Anderson, 2014; Mathewson et al, 2017; Van Lieshout et al, 2018). Structural and diffusion MRI (sMRI and dMRI) support the conceptualisation of atypical brain growth after preterm birth as a process characterised by micro-structural alteration of connective pathways due to impaired myelination and neuronal dysmaturation (Boardman et al, 2006; Anjari et al, 2007; Counsell et al, 2008; Ball et al, 2013; Back and Miller, 2014; Van Den Heuvel et al, 2015; Eaton-Rosen et al, 2015; Thompson et al, 2016; Batalle et al, 2017; Telford et al, 2017; Batalle et al, 2018); and the ensuing ‘dysconnectivity phenotype’ could form the basis for long term functional impairment (Boardman et al, 2010; Caldinelli et al, 2017; Keunen et al, 2017; Cao et al, 2017; Batalle et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%